Association of malnutrition with in-hospital and long-term outcomes among ST-elevation myocardial infarction patients receiving primary PCI. (3rd October 2022) - Hosseini, F; Pitcher, I; Kang, M; MacKay, M; Singer, J; Lee, T; Madden, K; Cairns, J; Wong, G; Fordyce, C
Abstract: Background: The impact of malnutrition on outcomes in a contemporary ST-segment-elevation myocardial infarction (STEMI) population is unclear. We hypothesized that malnutrition severity amongst STEMI patients undergoing primary percutaneous coronary intervention (pPCI) is associated with worse long-term outcomes. Purpose: The aim of this study was 2-fold: 1) to establish the prevalence of malnutrition among STEMI patients undergoing pPCI; 2) to determine the association of malnutrition severity on in-hospital and 1-year outcomes in STEMI patients receiving pPCI Methods: We retrospectively identified 1, 169 STEMI patients of age ≥65 years who had received pPCI (2013–2020). Patients who had presented with out-of-hospital cardiac arrest or those who received fibrinolytic therapy were excluded. The Controlling Nutritional Status (CONUT) score, based on serum albumin, total cholesterol and lymphocyte count, was used as a tool to assess the nutritional status of included patients. Malnourished patients were defined as those with a CONUT score of 5 to 12. To account for the impact of frailty, a frailty index (FI) was determined using the health deficit accumulation model (Table 1). The primary outcome was 1-year all-cause mortality. The secondary outcome was a composite of in-hospital heart failure, cardiogenic shock, re-infarction, major bleeding, stroke, and all-cause mortality. A multivariable model adjusting for baseline covariates, including frailty index score, was performed (Figure 1). Results: Among 1, 169 STEMI patients receiving pPCI, 315 (26.9%) were classified as malnourished. Malnourished patients were older (mean 77.4 vs. 76.0 years, p=0.009) and had a higher comorbidity burden. After multivariable adjustment, worsening malnutrition was associated with increased 1-year all-cause mortality (odds ratio [OR] = 1.29, p<0.001). Worsening malnutrition was also associated with a higher incidence of the in-hospital composite adverse outcome (OR = 1.12, p=0.003) and increased in-hospital all-cause mortality (OR=1.41, p<0.001). Conclusion: Among STEMI patients receiving pPCI, 1 in 4 were malnourished. Malnutrition was associated with increased rate of in-hospital composite adverse outcome and worse long-term outcomes, even when accounting for frailty. Efforts to routinely identify malnourished STEMI patients and to implement best practices to reduce the risk of adverse events in this vulnerable population are warranted. Funding Acknowledgement: Type of funding sources: None.